Intelligent Development and Connectedness in the Context of the Regional Development - Tsonkov, Nikolay; Petrov, Kamen; Berberova–Valcheva, Tzvetelina (UNWE Yearbook, 2023)
At present spatial development, the focus of the research, is directed to the regions’ development and establishing competitive environment of their territory. In this exposition the authors explore innovations and their influence on regional development improvement. The purpose of the research is the potential of the investment policies and innovative environment for creating terms of life quality increasing in regions. The authors try to create a methodology for enforcing the process of the regions’ intelligent development. The authors outline the tendencies related to regional intelligent development and influence on national territory development.